2‐phenylethynesulphonamide (PFT‐μ) enhances the anticancer effect of the novel hsp90 inhibitor NVP‐AUY922 in melanoma, by reducing GSH levels. (May 2016) - Yeramian, Andree; Vea, Alvar; Benítez, Sandra; Ribera, Joan; Domingo, Mónica; Santacana, Maria; Martinez, Montserrat; Maiques, Oscar; Valls, Joan; Dolcet, Xavier; Vilella, Ramón; Cabiscol, Elisa; et al.
Summary: Heat shock proteins (HSPs), are molecular chaperones that assist the proper folding of nascent proteins. This study aims to evaluate the antitumour effects of the hsp90 inhibitor NVP‐AUY922 in melanoma, both in vitro and in vivo. Our results show that NVP‐AUY922 inhibits melanoma cell growth in vitro, with down regulation of multiple signalling pathways involved in melanoma progression such as NF‐ĸB and MAPK/ERK. However, NVP‐AUY922 was unable to limit tumour growth in vivo. Cotreatment of A375M xenografts with NVP‐AUY922 and PFT‐μ, a dual inhibitor of both hsp70 and autophagy, induced a synergistic increase of cell death in vitro, and delayed tumour formation in A375M xenografts. PFT‐μ depleted cells from the reduced form of glutathione (GSH) and increased oxidative stress. The oxidative stress induced by PFT‐μ further enhanced NVP‐AUY922‐induced cytotoxic effects. These data suggest a potential therapeutic role for NVP‐AUY922 used in combination with PFT‐μ, in melanoma.